ANALISIS SEMIOTIKA PEIRCE PAKAIAN JENIS GAMIS SEBAGAI REPRESENTASI BUDAYA ARAB - Ruzqiyah Ulfa (Universitas Bunda Mulia, 2016)
Since at least 170 thousand years ago, humans have begun to use clothes and attaching meanings on it. The dynamics of the contemporary socio-religious phenomena bring back robe among the people in Indonesia, especially men. The author uses the theory of Peirce's triadic semiotic analysis of the robe and clothing to determine whether there has been a shift in the meaning of the robe worn in Arabic with the robe worn in Indonesia. Pictures of the robe of the two cultures were analyzed by looking at the icons, indices, and symbols that make up the meaning of the robe. Culture itself is defined as a system of socially transmitted behavior to the symbol as an element of the highest culture. Images for analysis were taken from internet sources with the aim to sample in order to gain a high diversity of function of the robe. The author managed to collect 11 pictures of the robe worn in the Arab and 14 pictures of the robe worn in Indonesia. From the results of analysis show that the robe in Arabic means: show the practical value of doing business, showing Arab rule over another nation, to build Arab unity, became a patron family, running life casually, simplicity, pattern, religiosity, conformity, social status, and worship. Comparison with the robe worn in Indonesia found that nine out of eleven this meaning has shifted while two meanings: simplicity and worship, still remains the same as in Arabic, even more strengthened. As for the meaning of the robe in Indonesia include leadership race, diversity in dress, understanding of Islam is low, part of the force, covering misconduct, acculturation, identity, religiosity, modesty, sexual strategy, social status, enlightenment, repentance, everyday life in pesantren and tolerance. Factors that cause a shift in the meaning of this form are physical and cultural factors.Keywords: Robe, Semiotics, Arab, Religiosity, Acculturation